Identifying Silver Linings During the Pandemic Through Natural Language Processing - Lossio-Ventura, Juan Antonio; Lee, Angela Yuson; Hancock, Jeffrey T.; Linos, Natalia; Linos, Eleni (Frontiers in Psychology, 2021)
COVID-19 has presented an unprecedented challenge to human welfare. Indeed, we have witnessed people experiencing a rise of depression, acute stress disorder, and worsening levels of subclinical psychological distress. Finding ways to support individuals’ mental health has been particularly difficult during this pandemic. An opportunity for intervention to protect individuals’ health & well-being is to identify the existing sources of consolation and hope that have helped people persevere through the early days of the pandemic. In this paper, we identified positive aspects, or “silver linings,” that people experienced during the COVID-19 crisis using computational natural language processing methods and qualitative thematic content analysis. These silver linings revealed sources of strength that included finding a sense of community, closeness, gratitude, and a belief that the pandemic may spur positive social changes. People’s abilities to engage in benefit-finding and leverage protective factors can be bolstered and reinforced by public health policy to improve society’s resilience to the distress of this pandemic and potential future health crises.